The Addition of Ammonia Solution with Different Concentrations in the Sperms on the Percentage Ovulation Egg of Abalone, Haliotis asinina - Suminto Suminto; Agus Archan Nuriman; Diana Chilmawati (Fakultas Perikanan dan Ilmu Kelautan, Universitas Diponegoro, 2009)
The aim of this research was to know the impact of addition of ammoniak in different concentration in the sperm on the percentage of egg ovulation. The research method was carried out by completely randomized design with four treatments and three replicates, respectively. Those treatments were the addition of ammoniac solution with concentration of 0% (treatment A), 0.005% (treatment B), 0.010% (treatment C), and 0.015% (treatment D). The data was analyzed by using ANOVA and Duncan’s Multiple Range Test to know the effect of between the other treatments. The results showed that was the highly significant difference effect (p<0.01) on the egg ovulation of Abalone (H. asinina). The highest egg ovulation rate was obtained in treatment B (94.67% ). The ovulation rate was significantly higher than those in treatments C, D, and A, respectively. According to the results, the best concentration of the ammonia solution to the abalone sperm added was 0.005%. Furthermore, the regression test also showed a positive, linear relationship between spermatozoa motility rate and egg ovulation rate. However, the analysis of orthogonal polymonial provided a ammonia solution with the highest ovulation rate of 0.0057%. Keywords: Concentration, ammonia solution, ovulation egg, abalone, H. asinina